ANALISIS SPASIAL KESESUAIAN BUDIDAYA KERAPU BERBASIS DATA PENGINDERAAN JAUH (STUDI KASUS: PULAU AMBON MALUKU) - Anggraini, Nanin; Adawiah, Syifa Wismayati; Ginting, Devica Natalia Br; Marpaung, Sartono (Institut Teknologi Sepuluh Nopember, 2019)
Indonesian waters have abundant marine aquaculture potential. This activity need to be maximized with remote sensing technology approach to determining locations that have the potential aquaculture areas. The research location is Ambon Island, Maluku Province. The method used for suitability site is Weighted Overlay Technique from biophysical parameters such as total suspended solids (TSS), sea surface temperature (SST), chlorophyll, and bathymetry. In addition, mangrove and coral reef data are used as a limiting factor for the suitability site. Based on the results of processing data, classes were quite suitable dominated in Piru Bay, Banguala Bay, and Ambon Bay; the appropriate classes were detected in Ambon Dalam Bay, and very suitable classes were detected in Piru Bay and Ambon Bay. The results of field measurement verification showed that the temperature of the image data with the insitu data correlated with the value of R2 0.74 and TSS image with insitu data shown R2 of 0.63.